A more sensitive detection of micrometastases of NSCLC in lymph nodes using the one-step nucleic acid amplification (OSNA) method - Vodicka, Josef; Mukensnabl, Petr; Vejvodova, Sarka; Spidlen, Vladimir; Kulda, Vlastimil; Topolcan, Ondrej; Pesta, Martin (Journal of surgical oncology, 2018)
BACKGROUND: Detection of tumor cells in lymph nodes (LNs) removed during the treatment of pulmonary tumor by radical surgery is limited by the possibilities of standard histopathological methods. The goal of this study was to obtain more accurate pTNM status by a more sensitive detection of micrometastases in LNs. METHODS: A total of 885 LNs, an average of 13.8 LNs per patient, were removed during 64 surgeries. LNs from the same zone were pooled together as a group, five groups of LNs were examined in each patient. A total of 320 groups of LNs were examined. One-step nucleic acid amplification (OSNA) method was compared to standard histopathological examination with haematoxylin-eosin (H&E) staining and CK19 immunohistochemistry, specifically by an ultimate analysis of all intraoperatively removed LNs. RESULTS: Identical results for H&E and OSNA examinations were recorded in 286 groups of LNs (89.4%). In total, positive examinations were recorded in 27 groups of LNs (8.4%) using the OSNA method, which were H&E negative. In seven groups of LNs (2.2%), the H&E examination was positive, while OSNA method produced negative results. CONCLUSIONS: The OSNA examination led to a higher pTNM stage classification in 14 (21.9%) patients. The clinical significance remains the subject of follow-up research.
Keywords: OSNA assay; Adenocarcinoma; nádory plic; nemalobuněčný karcinom plic; mikrometastázy; lung cancer; Lung Neoplasms; Humans; messenger RNA; lidé středního věku; Carcinoma, Non-Small-Cell Lung; Biomarkers, Tumor; cytokeratin 19; techniky amplifikace nukleových kyselin; Female; Aged; dospělí; senioři; lidé; pTNM; nádorové biomarkery; Adult; RNA, Messenger; Lymph Nodes; lymfatické uzliny; ženské pohlaví; Follow-Up Studies; Male; Middle Aged; prognóza; H&E; Nucleic Acid Amplification Techniques; adenokarcinom; spinocelulární karcinom; Carcinoma, Squamous Cell; mužské pohlaví; prospektivní studie; Neoplasm Micrometastasis; Prognosis; následné studie; Prospective Studies